Improving Distance Education Through Effective Conduct of Learning Action Cell - Jobelle Culajara, Carla (ASEAN Journal of Education, 2023)
The impacts of the Learning Action Cell in the classroom context in overcoming instructional gaps and improving distance education in the new normal were conveyed in the study. During the school year 2021-2022, data and findings were acquired through online surveys and focus group discussions. This quantitative and qualitative design utilized an online survey questionnaire which was completed by 21 respondents and 4 LAC teacher-facilitators who contributed to the focus group discussion. Based on the results, the majority of the respondents were females ages 26-30 and 41-45 and they attended 1-5 LAC sessions in the school year. Learning Action Cell as a tool in improving distance education shows that through these LAC sessions knowledge is acquired that makes the teaching and learning effective and addresses the knowledge gaps and digital divides. The LAC sessions through monthly/quarterly/yearly training programs received a weighted mean of 4.57. Moreover, LAC sessions can help the teacher in monitoring students’ data and achievement through varied activities and constant communication by enhancing their skills and knowledge in using available online and offline apps with a weighted mean of 4.57. While in the topic of assessment and evaluation, applying various assessments acquired in the LAC sessions received a weighted mean of 4.57. One of the obstacles to teachers in improving distance education is a loss of focus to finish their assignments because they have a lot of activities/programs to implement but can’t do it all at once owing to other work-related obligations. Two themes emerged from the perspectives of the four participants in the focus group discussion: ICT adoption and instructional efficiency. This implies that everyone will be imaginative and collaborative in improving distance education to reach every student through the Learning Action Cell. This study serves as the foundation for future research into the Learning Action Cell.